Determinants of FinTech products and services adoption in Kingdom of Saudi Arabia (KSA) / Alamoodi, Mohammed Abdul Khaleq Abdul Rahman and Zarehan Selamat - Alamoodi,; Abdul Rahman, Mohammed Abdul Khaleq; Selamat, Zarehan (Faculty of Business and Management, 2021)
This research focuses on the factors that influence Fintech products and services adoption among bank customers in the Kingdom of Saudi Arabia. The extended technology acceptance model (TAM) was employed to determine attributes affecting the adoption of Fintech in Saudi Arabia perspective. The online survey was conducted to collect information on demographic factors and their intentions to adopt FinTech products and services. 300 responses were gathered and their intention to adopt FinTech products are measured by using five Likert Scale to which respondents were required to indicate their agreement or disagreement on perceived ease of use (PEoU), perceived usefulness (PU), social influence (SI), and security concern (SC). The result shows that PU and SI significantly influenced the adoption of FinTech. The findings of this research would be valuable to policy-makers in Saudi Arabia by helping them to determine the variables that have a significant effect on the process of adoption and establish some future potential guidelines for FinTech firms to boost their intention to embrace FinTech in the Kingdom of Saudi Arabia.